Improved Sensing Properties of Thermal Conductivity-Type CO2 Gas Sensors by Loading Multi-Walled Carbon Nanotubes Into Nano-Al2O3 Powders - Shen, Bin; Zhang, Fang; Jiang, Leiming; Liu, Xinlei; Song, Xiaoyang; Qin, Xianli; Li, Xuewei (Frontiers in Energy Research, 2021)
In order to solve the slow-response problem of traditional bead-type thermal conductivity CO2 sensors, a fast-response thermal conductivity CO2 sensors can be made by using multiwalled carbon nanotubes (MWNTs) to modify the performance of the sensor carrier. The carrier material, nanoscale γ-Al2O3/CeO2 powder, was synthesized by chemical precipitation, and its particle size was found to be 20-50 nm through SEM. After the carrier material was wet incorporated into carbon nanotubes, the composite carrier γ-Al2O3/CeO2/MWNTs was obtained. Black-black element process was adopted to reduce the influence of radiant heat. The results show that the designed thermal conductivity sensor has a fast response to CO2 gas, with a 90% response time of 9s and a recovery time of 13s, compared to major commercial Carbon dioxide sensors. There is a good linear relationship between the sensor output and CO2 gas concentration, with an average sensitivity of 7.4 mV/10% CO2. Thus, the response speed of a thermal conductivity sensor can be enhanced by doping carbon nanotubes into nano-γ-Al2O3/CeO2.